2020
DOI: 10.1002/mp.14407
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of dynamic flat‐panel detector‐based chest radiography with nuclear medicine ventilation‐perfusion imaging for the evaluation of pulmonary function: A clinical validation study

Abstract: Purpose: Dynamic chest radiography (DCR) is a flat-panel detector (FPD)-based functional lung imaging technique capable of measuring temporal changes in radiographic lung density due to ventilation and perfusion. The aim of this study was to determine the diagnostic performance of DCR in the evaluation of pulmonary function based on changes in radiographic lung density compared to nuclear medicine lung scans. Methods: This study included 53 patients with pulmonary disease who underwent DCR and nuclear medicine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 24 publications
(31 reference statements)
2
18
0
Order By: Relevance
“…Other types of functional maps can be created using specific images depending on the purpose. In addition, ventilation-perfusion (V/Q) mismatch can be evaluated by combining ventilation and perfusion imaging using DXR ( 2 66 67 68 ). V/Q mismatch is an important diagnostic factor for treatment strategy, and scintigraphy is generally used in the clinical setting ( 69 70 ).…”
Section: Perfusion and V/q Mismatch Imagingmentioning
confidence: 99%
“…Other types of functional maps can be created using specific images depending on the purpose. In addition, ventilation-perfusion (V/Q) mismatch can be evaluated by combining ventilation and perfusion imaging using DXR ( 2 66 67 68 ). V/Q mismatch is an important diagnostic factor for treatment strategy, and scintigraphy is generally used in the clinical setting ( 69 70 ).…”
Section: Perfusion and V/q Mismatch Imagingmentioning
confidence: 99%
“…For example, recent animal studies have indicated that changes in radiographic lung density correlated strongly with both blood and inspired air volume, and that functional abnormalities such as limited air flow, trapped air, and pulmonary embolism, could be detected as decreased changes in radiographic lung density, even with no use of radiopharmaceutical and contrast agents (30,31). Moreover, a preliminary clinical study found a high correlation between changes in radiographic lung density and the total accumulation of radioactive agents at the lobar/whole-lung level, and demonstrated the feasibility of DCR-derived ventilation-perfusion studies (32). These findings highlight the ability of DCR to provide ventilation and perfusion metrics on the basis of changes in radiographic lung density.…”
Section: Introductionmentioning
confidence: 79%
“…Except for the breathing, the setting was the same as for conventional chest radiography; the imaging was performed in a posteroanterior (PA) direction with the patient in a standing position. Details of DCR have been described previously (19,32). The patients were instructed to take a forced breathing under automated voice guidance.…”
Section: Dcrmentioning
confidence: 99%
See 1 more Smart Citation
“…Pulmonary perfusion and ventilation images were created from chest digital dynamic radiography (DDR), captured using a flatpanel detector (AeroDR fine; Konica Minolta, Inc., Japan) and an X-ray system (RADspeed Pro; Shimadzu Corporation, Japan) using KINOSIS 1.00 (Konica Minolta, Inc.). DDR technology is a novel evaluation of pulmonary perfusion and ventilation that provides a functional assessment in 6-15 sec with no contrast agent [1,2]. It can be performed in standing or supine position [2] and requires less radiation exposure than scintigraphy.…”
Section: Clinical Imagementioning
confidence: 99%